Creation methodology for calculating methane low-flow low-speed compressor stages based on data processing of experimental study - S. S. Busarov; I. S. Busarov; A. V. Nedovenchany; R. E. Kobylskiy; A. A. Kapelyukhovskaya; E. V. Zaushitsyn; A. Yu. Gromov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This article presents the results of a set of works carried out to adapt the existing mathematical model for calculating the working processes of low-speed compressor stages for methane compression and to create an engineering methodology for calculating the performance of the stage based on the experimental data obtained.